Value of emergency toxicological investigations in differential diagnosis of coma. Issue 6194 (6th October 1979) - Helliwell, M; Hampel, G; Sinclair, E; Huggett, A; Flanagan, R J
Abstract : Out of 208 cases of coma of unknown aetiology referred to the poisons unit of this hospital during 1978 for emergency toxicological investigations, 108 were found to be due to self-poisoning medical conditions, mainly neurological, accounted for coma in 90 patients; the cause was not ascertained in the remaining 10 cases. More than one preparation had been ingested by 58 (54%) of the poisoned patients, although barbiturates were the drugs most commonly encountered in the severe cases. Toxicological investigations should be considered in the differential diagnosis of coma when history, physical examination, and emergency biochemical measurements yield little diagnostic information.